The Rhetoric of Preaching by AGH. Sanusi Baco - Muammar Tauhid; Nurhidayat Muhammad Said; Firdaus Muhammad (Jurnal Mercusuar, 2023)
This study uses a qualitative research type with literature research or library research focusing on the Rhetoric of AGH. Sanusi Baco's Da'wah. The approach used is the da'wah and communication approach. In this research, the researcher took primary sources in the form of lecture videos on YouTube and recorded lectures of AGH. Sanusi Baco. Secondary data sources are from other informants who are close to and understand the figure or results from other people's writings about the figure. In this research, the researcher took secondary sources from the results of other people's writings concerning AGH. Sanusi Baco. Data collection methods go through several stages, namely: collecting documents and videos on YouTube. Data analysis was done through three stages: taxonomic analysis, interpretative analysis, and synthetic analysis. The results of this study indicate that the da'wah rhetoric of AGH. Sanusi Baco's ethos can be seen that the credibility possessed by AGH. Sanusi Baco was attached from the beginning when he returned from studying at Al-Azhar University, Cairo, Egypt. Given his educational background, AGH. Sanusi Baco became a preacher with a unique style of conveying his da'wah. AGH. Sanusi Baco's pathos lies in the appeal of his da'wah, which has a distinct character, although sometimes the content of the lecture is repeated several times in different places with the same theme but remains captivating. His unique preaching style is calm, provides coolness, comfort, peace of mind, and is far from provocative matters or things leading to violence. AGH. Sanusi Baco's logos build his audience's awareness by adjusting the language and material he uses when lecturing. Thus, the language of da'wah carried out by the preacher is a language that is easily understood and logically accepted in the audience's mind. Not with manipulative language that dramatizes falsehoods and is beyond the logical reasoning of the audience. The implication of this research is that preachers or missionaries in today's era should be able to make AGH. Sanusi Baco as an example or role model in carrying out their da'wah activities. Preachers or missionaries are expected to align their verbal da'wah with their behavioral da'wah so that the audience can see that there is an example to be followed and applied in their daily life from what is conveyed by a preacher or missionary. Secondly, it's necessary for a preacher or missionary to possess the three rhetorical elements of Aristotle in his personality, namely ethos, pathos, and logos, as from this research, AGH. Sanusi Baco is a figure who possesses these three rhetorical elements. So, in the da'wah process, between the object (preacher) and the subject (audience), there is feedback from the presented da'wah.